MPS simulation on melt penetration of CAFÉ experiment at 1200 C - Asril Pramutadi Andi Mustari; Iksal Iksal; Sumiati Sumiati (Indonesian Journal of Physics, 2012)
After Fukushima accident, molten relocation inside the reactor is still unclear due to difficulties of detecting internal condition. Eutectic reaction is one of the main mechanism of internal structure liquefaction. Moving particle semi- implicit (MPS) is suitable of analyzing localized phenomena such as eutectic reaction due to its capability on simulating surface with large deformation. In this work, the MPS code for eutectic reaction was developed for calculating melting rate and its relocation process. Based on the MPS model, the CAFÉ core melt experiment was analyzed. For melting penetration rate of molten uranium into stainless steel at 1200 C, two dimensional MPS simulation predicted agreeable result.